Discourses on nations and identities - Syrovy, Daniel 1984- (Many languages of comparative literature, 2021)
The third volume of the collected papers of the ICLA congress "The Many Languages of Comparative Literature" includes contributions that focus on the interplay between concepts of nation, national languages, and individual as well as collective identities. Because all literary communication happens within different kinds of power structures - linguistic, economic, political -, it often results in fascinating forms of hybridity. In the first of four thematic chapters, the papers investigate some of the ways in which discourses can establish modes of thinking, or how discourses are in turn controlled by active linguistic interventions, whether in the context of the patriarchy, war, colonialism, or political factions. The second thematic block is predominantly concerned with hybridity as an aspect of modern cultural identity, and the cultural and linguistic dimensions of domestic life and in society at large. Closely related, a third series of papers focuses on writers and texts analysed from the vantage points of exile and exophony, as well as theoretical contributions to issues of terminology and what it means to talk about transcultural phenomena. Finally, a group of papers sheds light on more overtly violent power structures, mechanisms of exclusion, Totalitarianism, torture, and censorship, but also resistance to these forms of oppression. In addition to these chapters, the volume also collects a number of thematically related group sections from the ICLA congress, preserving their original context